2016
DOI: 10.1021/acsami.6b07740
|View full text |Cite
|
Sign up to set email alerts
|

On-Fly Femtosecond-Laser Fabrication of Self-Organized Plasmonic Nanotextures for Chemo- and Biosensing Applications

Abstract: Surface-enhanced Raman scattering (SERS) and surface-enhanced photoluminescence (SEPL) are emerging as versatile widespread methods for biological, chemical, and physical characterization in close proximity of nanostructured surfaces of plasmonic materials. Meanwhile, single-step, facile, cheap, and green technologies for large-scale fabrication of efficient SERS or SEPL substrates, routinely demonstrating both broad plasmonic response and high enhancement characteristics, are still missing. In this research, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
37
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(38 citation statements)
references
References 55 publications
1
37
0
Order By: Relevance
“…Surface-enhanced Raman scattering (SERS) is an ultra-sensitive non-invasive spectroscopic technique based on a label-free identification of different molecules placed in the vicinity of plasmonic-active nanostructured metallic substrates [1][2][3][4] . Intensity of the characteristic Raman signal defining the specific vibrational signatures of individual molecules is usually very weak.…”
mentioning
confidence: 99%
“…Surface-enhanced Raman scattering (SERS) is an ultra-sensitive non-invasive spectroscopic technique based on a label-free identification of different molecules placed in the vicinity of plasmonic-active nanostructured metallic substrates [1][2][3][4] . Intensity of the characteristic Raman signal defining the specific vibrational signatures of individual molecules is usually very weak.…”
mentioning
confidence: 99%
“…2a). It was also reported that the nanoscale morphology of the craters and their plasmonic properties could be tailored via their irradiation with a subsequent laser pulse with properly adjusted energy E 2 [35]. Figure 2(b,c) reveals how the nanoscale surface morphology evolves under irradiation of the imprinted crater with a second laser pulse at E 2 =240 nJ (the energy of the first pulse was fixed at E 1 =430 nJ).…”
Section: Properties Of Sers-active Site and Analyte-enrichment Systemmentioning
confidence: 86%
“…As a result, the ejected surface layer leaves a crater of a few microns in diameter and with multiple self-organized nanospikes. Such nanospike-based arrangements were shown to act as efficient plasmon-active nanostructures permitting to enhance photoluminescence and SERS signals from the attached emitters [35,36]. The maximum density of such nanospikes within a single crater (which would ensure the best SERS performance) was previously shown to be tuned by the size of the laser beam (or NA of the focusing lens) [36].…”
Section: Properties Of Sers-active Site and Analyte-enrichment Systemmentioning
confidence: 99%
“…As a result, the ejected surface layer leaves a crater of a few microns in diameter and with multiple self-organized nanospikes. Such nanospike-based arrangements were shown to act as efficient plasmon-active nanostructures permitting to enhance photoluminescence and SERS signals from the attached emitters [36,37]. The maximum density of such nanospikes within a single crater (which would ensure the best SERS performance) was previously shown to be tuned by the size of the laser beam (or NA of the focusing lens) [37].…”
Section: Properties Of Sers-active Site and Analyte-enrichment Systemmentioning
confidence: 99%
“…Therefore, to ensure a dense arrangement of the craters on the central site of the device without smoothing their surface morphology, we used laser projection lithography to generate a flat-top beam with sharp shoulders and a diameter of 2.5 µm (see Figure 2a). It was also reported that the nanoscale morphology of the craters and their plasmonic properties could be tailored via their irradiation with a subsequent laser pulse with properly adjusted energy E 2 [36]. Figure 2b,c reveals how the nanoscale surface morphology evolves under irradiation of the imprinted crater with a second laser pulse at E 2 = 240 nJ (the energy of the first pulse was fixed at E 1 = 430 nJ, while the time delay between two pulses was 5 ms).…”
Section: Properties Of Sers-active Site and Analyte-enrichment Systemmentioning
confidence: 99%